Prosthenorchis elegans-associated pyogranulomatous ileitis and colitis in a squirrel monkey (Saimiri oerstedii) - Alfaro, A. (2012)
An adult male squirrel monkey (Saimiri oerstedii) with posterior paresis, was submitted to the Pathology Department of the Veterinary Medicine School of the National University. The monkey presented peritonitis, adhesions in the ileum-colic area with severe chronic pyogranulomatous inflammation, associated to the presence of Prosthenorchis elegans. Besides, we found a focal demyelination at the thoraco-lumbar portion of the spinal cord probably associated with a previous trauma. Acanthocephaliasis associated to Prosthenorchis elegans is a common cause of pyogranulomatous ileitis and colitis in New and Old World non-human primates. In some cases this disease could progress to peritonitis, sepsis and even death.